Peningkatan Kapabilitas dan Performa UMKM melalui Monitoring dan Pendampingan - Fidiana Fidiana; Widhi Ariestianti Rochdianingrum; Endang Dwi Retnani; Dini Widyawati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
This community service activity is continuously carried out to develop the creativity of mothers in producing innovative and attractive products. This activity involves training and assistance in preparing financial and marketing reports. This activity was carried out in collaboration with the Sukolilo District and STIESIA Surabaya. MSMEs in Sukolilo District experienced several obstacles related to preparing financial reports, marketing that utilized social media, and other technical obstacles. After this mentoring activity, MSME managers gained several benefits, including having started compiling financial reports. Marketing training activities are carried out using Instagram social media as a means of producing products. In this activity, assistance was carried out to create an Instagram account, taking photos of products to be uploaded on Instagram, assisting in uploading product photos on Instagram accompanied by product descriptions so that they could attract consumers. This activity is carried out to improve the business carried out from the management aspect. The target to be achieved is that MSME players have financial reports that can be used to submit funds or capital to banks for business development, expand marketing networks, and increase sales.